Burial Mounds in Croatia: Landscapes of Continuity and Transformation - Potrebica, Hrvoje (Array, 2008)
This paper will primarily concentrate on burial mounds as agents in relation between prehistoric communities and landscape. It will explore the role of burial mounds in claiming, gaining and preserving control over landscape implemented by such communities through notions of identity and continuity. It will also address transformation of that role from early to late prehistoric periods in different areas of Croatia, based on fundamental chronological difference between the burial mounds in continental and coastal area of Croatia. While the appearance of such mounds in coastal areas can be established as early as the Early Bronze Age, in continental areas they appear only in the Early Iron Age with rather abrupt break in the middle of the last millennium B.C. and very short (and spatially rather limited) reappearance in the Roman period. Beside the obvious (and probably crucial) difference in available material used for erection of such monuments, this paper will explore other possible, non-environmental influences on their size, number and distribution. Although the source of such influences rested within the social framework of specific communities, material and anthropological content of such monuments is their only reflection, and therefore has to be included in this discussion. Another important element related to continuity and transformation of burial mounds is politics of their use and re-use in periods following their initial construction. This is even more interesting in cases when we can establish sequence of culturally and/or ethnically different communities in the same area ; or large time span between two major occupation periods.